Comparative Studies on the Elemental Analysis, Proximate Analysis, Antimicrobial Activity and Acute Toxicity Study of Picralima nitida Leaves and Seeds - Ogbeide, Osahon Kennedy; Unachukwu, Christabel Ifeoma; Sajere, Onome; Aghedo, Oscar Notoriuwa; Oghomwenrhiere, Osarinmwian; Dibie, Edward Nduka; Okuo, James Majebi (Sciences of Phytochemistry, 2026)
In West African cultures, Picralima nitida has long been used in medicine for providing pain relief, controlling inflammation, reducing fever, and fighting infections. This study compares the elemental and proximate compositions, antimicrobial activities, and acute toxicity of the leaf and seed extracts of P. nitida. The samples were extracted using the cold maceration method. Elemental analysis revealed high levels of magnesium, calcium, and potassium in the leaf extract, while the seed extract contained lower amounts. The leaves also had a higher crude fiber content (15.5%), whereas the seeds were richer in crude protein (19.47%) and ether extract (14.00%). The leaf extract prevented the growth of E. coli, S. aureus, and P. aeruginosa, yet did not affect C. albicans. The seed extract exhibited a broader and stronger inhibitory effect against P. aeruginosa. The minimum inhibitory concentrations (MICs) of E. coli and P. aeruginosa were both 100 mg/mL (15.00 mm inhibition zone) when tested with the leaf extract, whereas S. aureus had an MIC of 75 mg/mL (13.00 mm inhibition zone). The MICs of the seed extract were 25 mg/mL (9.00 mm inhibition zone) for E. coli and S. aureus, 75 mg/mL (18.40 mm inhibition zone) for P. aeruginosa, and 25 mg/mL (11.20 mm inhibition zone) for C. albicans. For the toxicity tests, the leaf extract appeared safer for animals (mice) with no adverse effect at an LD₅₀ of 800 mg/kg, whereas the seed showed a notable adverse effect with an LD₅₀ of ≥283 mg/kg. These experimental findings show the health benefit of P. nitida leaves and seeds in traditional medicines and its potential as an anti-microbial agent and use for dietary purposes.